Implementation of Lean Principles in Building Construction Industry, Sri Lanka - H.M.K.A. Senevirathne; B.A.D.S. Wimalasena (Advances in Technology, 2025)
Lean construction has been introduced into the Sri Lankan construction industry to address critical challenges, including waste management and high construction costs due to high material costs and lack of skilled labor. The aim of this study is to investigate the extent to which lean construction is implemented in the Sri Lankan building construction industry. This paper presents the findings of a study that investigated the state of lean construction implementation in the Sri Lankan building construction industry using quantitative and qualitative research methods. A questionnaire survey was conducted to obtain the opinions of construction professionals on the types of tools and techniques that support the implementation of lean construction, stages of application of lean methods, and benefits of lean construction to the projects. In addition, interviews were carried out to obtain expert views on the implementation of lean construction, including challenges encountered in the Sri Lankan building construction industry. Primary data collected include 51 completed questionnaires and five expert interviews with building construction industry professionals using a simple random sampling method. The collected data were analyzed using descriptive analysis and the chi-square goodness of fit test. The investigation revealed that the 5S concept is the most used lean tool in the industry. It was also revealed that many of the lean methods are applied during the construction stage knowingly and sometimes unknowingly. It is important to note that the results suggest that the reduction of waste is the dominant benefit that the building construction industry receives due to the adaptation of lean construction techniques in Sri Lanka. Lack of technical knowledge, employee resistance to adapting to lean culture, and lack of cooperation were identified as the main challenges. Overall, this study reveals moderate awareness among Sri Lankan construction industry professionals of lean construction and the findings will help the Sri Lankan construction industry to establish strategies for implementing lean construction in line with their project goals to achieve higher productivity.